The Effect of Global Commodity Prices and JCI on Mutual Fund Investments in Indonesia 2013-2023 - Mega Mustika Gustinanda (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Technological developments support the digitalization of investment instruments. Hence, investment in mutual funds is one of the instruments that has experienced a positive trend and can survive economic instability. The success of mutual fund investment in surviving economic instability results from investment managers' performance in diversifying portfolios during that period. This study aims to determine the impact of global commodity prices on mutual fund net asset value. The analysis models used in this research are the Bergandi regression analysis estimation model and the classical assumption test. This research uses time series data from the period of 2013 to 2023. The results obtained in the study show that global commodity prices have an impact on the net asset value of mutual funds. In contrast, the Composite Stock Price Index (CSPI) and gold prices have a significant positive impact, world oil prices have a negative effect, and nickel prices and palm oil prices do not influence mutual funds' net asset value (NAV).